Characterization of an RNA-directed DNA polymerase found in association with murine intracytoplasmic A-particles. - Kohno, M (1977)
An RNA-directed DNA polymerase was found to be associated with intracytoplasmic A-particles from DBA/2 mouse leukemia cells. The enzyme activity was detected after disrupting the purified particles with 2 M NaCl-20 mM dithiothreitol. The presence of a divalent cation and all four deoxyribonucleoside triphosphates was essential for this enzyme activity. The enzyme had a clear preference for Mg2+ over Mn2+. Cesium sulfate isopycnic gradient centrifugation of the DNA product synthesized in the actinomycin D-containing reaction revealed the presence of DNA-RNA hybrid. Furthermore, the purified DNA product was found to hybridize with RNA isolated from A-particles. These observations strongly indicate that the endogenous A-particle RNA serves as the template for the DNA polymerase.